(untitled) (Heritage, 2024)
Every legal system, which rests on the foundations of the rule of law and strives for the principle of legal certainty, tends to achieve an efficient system of accountability to the greatest extent possible. A detailed analysis and comparison with good practices of other legal systems offers opportunities for specifying the directions of reforms that would improve accountability in public administration. The analysis of certain aspects of the accountability of public officials in French law contributes to a deeper understanding of the accountability of public administration, thus offering examples of good practice that can serve to improve accountability in Serbian public administration.